KARAKTERISTIK FISIKOKIMIA PATI AREN ASETAT - I Kadek Agus Heriawan; Abdul Rahim; Syahraeni Kadir (Universitas Tadulako, 2016)
The purpose of the research was to identify the physicochemical characteristics of acetatedarenga starch produced by way ofan acetylation technique. This study used a completely randomized design (CRD) with treatments consisted of five different time lengths of reaction between the arenga starch and acetic anhydride 5 % i.e. 15, 30, 45, 60 and 75 minutes. The reaction between the arenga and the acetic anhydride 5% was being maintained at pH 8.0-8.5. The research resultsshowed that theacetatedarenga starch contained 6.69% of water, a viscosity of 376 cp and emulsion stability of 74.00%. The viscosity of the acetated arenga starch produced is stable suggesting that this substance is suitable to be utilized in food processing. Key Word: Acetated arenga starch, Emulsion, Physicochemical and Viscosity.